PEDAGOGICAL CONTENT THREE-FACTOR MODEL OF EDUCATING HIGH-SCHOOL STUDENTS FOR PROFESSIONAL ACTIVITIES - T. A. Lopatukhina; A. V. Rynkevich (Russian State Vocational Pedagogical University, 2016)
The aim of the presented publication is to discuss the changes in the practice of professional higher education which consist in strengthening and emphasis of an educational component in educational process.Methods. The methods involve the analysis of a condition of higher education and the provisions of the Federal Law on Education regulating its functioning in the Russian Federation; text-centered approach to education of the person of culture - the professional specialist, responsible for the activities.Results and scientific novelty. It states that some drawbacks of the existing present-day education organization are being constantly discussed by a pedagogical community of the Russian Federation: the absence of development stability; the absence of effective strategies and technologies of their implementation; the triumph of national nihilism confirmed by high schools and individual scientists participation in different foreign educational projects, usually having world notorious reputation; penetration of commercial principals in to an education system, the latter having been turned in to an education service, etc. As a result the personality quality itself has greatly deteriorated as well as Russia society intellect, on the whole, according to some law, psychological, philosophical and pedagogical analysis. The article stresses that the way out maybe found in restoring Russian national traditions and lost values and returning them to Russian education via adequate upbringing process. The authors describe their innovative model comprising three directions: 1) the integral three-factor spiritual, moral and intellectual upbringing of the students; 2) specially selected text content professional information using text-centered approach and 3) peculiar interaction of two education subjects: a student and a teacher. Their cooperation envisages the following stages: first, teacher's strict guidance of a student; then - teacher's soft support of a student; after this - teacher's accompanying a student at a special request and, at last, - wise consulting a student if needed. In the long run, in the author's opinion, this system should succeed in creating some special platform for student's further self-upbringing and self-learning. The model described in the paper is considered on the example of the discipline «A foreign language in the professional sphere». The just described model was worked out for effective foreign language education process perceived as a part of professional high-school education. Due to this system, foreign language becomes a source of professionally demanded and personally valuable information. Practical significance. The model provided in the paper gives the chance to the student to be lifted to self-education level, to plan professional self-development and to build an individual trajectory of professional career.